A Numerical Study of the Formation of Summertime Arctic Stratus Clouds - Ohta, Sachio (1981)
P(論文) A numerical study was made on the formation of summertime arctic stratus clouds which are considered to be generated due to cooling of the warm moist air advected over the polar ice from the surrounding area of the arctic ocean. A model was constructed in which a system of equations for a steady-state planetary boundary layer on cloudy days is transformed into a one-dimensional, time-dependent system of equations by introducing the downstream derivative where the time corresponds to the travel time moving with the geostrophic wind velocity. Eddy diffusivities which were obtained by KONDO from measurements under strongly stable conditions in the atmospheric surface layer are adopted in the calculation. Upon using the method of P_3 approximation for calculating the equation of radiative transfer, the radiative effects are incorporated into the model including scattering, absorption and emission of radiation by cloud droplets as well as absorption and emission of radiation by gaseous constituents. With this model a simulation was carried out for the U.S. standard atmosphere, Arctic, July as an initial condition. The results of calculation are as follows. The cloud appears at a height about 70m because of the lowering ground surface temperature. After the cloud formation, on account of intense radiative cooling near the top of the cloud the temperature decreases greatly and the condensation of water vapor is much enhanced. After 24 hours the temperature at the surface remains at a constant value of melting ice, while in the cloud it falls rapidly. Consequently, the cloud temperature becomes lower than that of the surface. This creates the transport of water vapor from the surface into the cloud and then accelerates the condensation of it. Because of intense radiative cooling, the temperature shows a sharp inversion in the upper layer of the cloud. As the radiative temperature change has a maximum cooling rate in this temperature inversion layer, the temperature in this layer falls down remarkably and more ...